Spin hall magnetoresistance and spin seebeck effect in Pt|CoCr2O4 heterostructures - Aisha Aqeel; Matthias Kronseder; Nynke Vlietstra; Hans Huebl; Jeroen A. Heuver; Beatriz Noheda; Javier Herrero-Martín; Eric Pellegrin; Hari B. Vasili; Maxim Mostovoy; Christian Back (Science and Technology of Advanced Materials)
This study delves into spin current-induced phenomena, such as spin-Hall magnetoresistance and the spin Seebeck effect within Pt films deposited on a noncollinear magnet, CoCr[Formula: see text]O[Formula: see text] (CCO), particularly at low temperatures. Detailed investigation of the angular dependencies of spin Hall magnetoresistance (SMR) and spin Seebeck effect (SSE) was carried out. The temperature-dependent behavior of both SMR and SSE signals exhibits a discernible variation correlated with different magnetic phases of CCO. To distinguish the contributions arising from magnetic proximity effects, we conducted X-ray magnetic dichroism (XMCD) at the Pt-M[Formula: see text] edge. XMCD data from Pt/CCO heterostructures suggest that any magnetic moment associated with Pt, if present, is below the detection limit. This supports the notion that the observed signals primarily stem from SMR and SSE. This study offers insights into spin-current-driven phenomena, paving the way for potential spintronic applications.